Poverty and Data Accuracy as Public Administration Issues: A Study on Social Policy in Banyumas Regency - Atika, Zaula Rizqi (Public Policy and Management Inquiry, 2025)
This article explores the issue of poverty in Banyumas Regency within the framework of public administration, with a particular emphasis on the accuracy and consistency of poverty data as a foundation for formulating social policies. Employing a qualitative descriptive approach with purposive sampling techniques, the study uncovers discrepancies in poverty indicators and measurement approaches across local government units. These data inconsistencies significantly impact the accuracy of targeting social programs, thereby hindering the effectiveness of public policy implementation. Furthermore, the findings reveal that the problem is not merely technical but also indicative of weak data governance and poor inter-institution coordination. Therefore, the integration of data systems and harmonization of poverty indicators among institutions are crucial for supporting targeted, equitable, and data-driven policymaking.